The Development of Video as a Guidance and Counseling Media to Develop Student Creativity - Maryam Rahim; Tuti Wantu; Jumadi Mori Salam Tuasikal; Mardia Bin Smith (Biblio Couns : Jurnal Kajian Konseling dan Pendidikan, 2021)
The limited learning media also affects the efforts of teachers to develop student creativity. On the basis of this condition, it is deemed necessary to develop a creativity development video that can be used by teachers, so that education as an effort to develop student potential optimally can achieve the expected results. In addition to being a medium used by the teacher, the video is meant to be used by students independently. This study aims to produce videos as a medium of guidance and counseling for the development of creativity of junior high school students. This study uses development research based on the stages of research by Sugiono. This study uses a quisioner as a data collection technique. Research activities include: (1) identifying problems in the field related to creativity development activities carried out by junior high school teachers, (2) analyzing the substance of the activity, (4) developing the initial video design, (5) developing expert validation instruments on the initial video design that has been developed , (6) carry out expert validation and revisions, (7) carry out small group trials and revise the final product. This research and development has produced a creativity development video that has gone through expert validation and small group trials, in the sense that it is suitable for use by teachers as a medium in developing the creativity of junior high school students.